An Application of the Marketing Mix and Online Marketing as a Business Strategy for SMME Cafes in South Africa - Gujral, Meenakshi; Rauzela, Monwabisi; Chuchu, Tinashe (Journal of Economics and Behavioral Studies, 2016)
The objective of the study was to examine the impact of marketing mix and online marketing on SMME cafes in South Africa as a marketing strategy. The study was an exploratory research design which sought to get new insights into the activities of how marketing strategies could be adopted into the SMME’s in South Africa. Convenience sampling technique was used in selecting 5 small to medium cafes from Braamfontein, located in the Centre of Johannesburg, South Africa. Data was collected from both primary and secondary sources. Primary data was in form of focused group discussions and interviews to elicit information for the study, while the secondary data was culled from other related works, libraries as well as information from the internet. Qualitative research approach was adopted in analysis of the data. The study has proven that cafe owners or brand strategists do implement an integrated marketing strategy embracing both marketing mix and online marketing. The study also revealed that, online marketing was an effective platform to help communicate a desired message to the target audience. The study recommended for marketers to recognize the importance of embracing and employing an integrated marketing strategy. There is also the need for cafe owners to be effective in using integrated marketing strategy.